Taxonomic study and morphology based phylogeny of the patagonic clade Liolaemus melanops group (Iguania: Liolaemidae), with the description of three new taxa - S., Abdala C.; Semhan, R. V.; Azocar, D. L. Moreno; Bonino, M.; Paz, M. M.; Cruz, F. (Zootaxa, 2012)
The genus Liolaemus is a group of lizards with more than 230 recognized species, which have been grouped in differentclades and subgroups. One of the monophyletic groups is the one of Liolaemus boulengeri or “the patch group”; this cladeitself is integrated by several monophyletic groups: the groups Liolaemus anomalus, Liolaemus wiegmanii, Liolaemusdarwinii and Liolaemus melanops. The latter group is constituted almost exclusively by Patagonian lizards, and it is ourfocal group. In the present work we describe three new species belonging to the Liolaemus melanops group. One of thenew taxon described, Liolaemus tromen sp. nov., is related to the Liolaemus fitzingerii clade, inhabits in the Center-Westof Neuquén Province, and was confused initially with Liolaemus hermannunezi, a mountain Chilean species. The secondspecies described, Liolaemus purul sp. nov., belongs to the Liolaemus telsen clade, inhabits in the center and north-westof Neuquén Province, and was confused first with Liolaemus boulengeri and then with Liolaemus loboi. While the thirdspecies, Liolaemus dumerili sp. nov., is basal of the L. goetschi group, inhabits in the center-south of Río Negro provinceand was considered as Liolaemus melanops. In addition, we present a phylogenetic analysis based in the morphology and we contribute with a dichotomic key for males of the Liolaemus melanops group.